2015
DOI: 10.1002/chem.201501249
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Plasticity in Glycomimetics: Fluorocarbamethyl‐L‐idopyranosides Mimic the Intrinsic Dynamic Behaviour of Natural Idose Rings

Abstract: Sugar function, structure and dynamics are intricately correlated. Ring flexibility is intrinsically related to biological activity; actually plasticity in L-iduronic rings modulates their interactions with biological receptors. However, the access to the experimental values of the energy barriers and free-energy difference for conformer interconversion in water solution has been elusive. Here, a new generation of fluorine-containing glycomimetics is presented. We have applied a combination of organic synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 54 publications
4
14
0
1
Order By: Relevance
“…Also, idosamine possesses increased flexibility that leads to two interchanging chair conformations. Recent studies revealed that gem ‐difluoro‐carbamethyl‐ l ‐idopyranosides mimic this natural behavior, which confirms our findings on mono ‐fluoro‐carba‐ l ‐idosamine . The influence of the phosphate at C6 on activity is evident (Figure ), and is also reflected by the comparison of 18 and 1 .…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Also, idosamine possesses increased flexibility that leads to two interchanging chair conformations. Recent studies revealed that gem ‐difluoro‐carbamethyl‐ l ‐idopyranosides mimic this natural behavior, which confirms our findings on mono ‐fluoro‐carba‐ l ‐idosamine . The influence of the phosphate at C6 on activity is evident (Figure ), and is also reflected by the comparison of 18 and 1 .…”
Section: Resultssupporting
confidence: 90%
“…Thus, the coupling constants of 14 and 2 are significantly higher than the calculated values for methyl β‐ l ‐idopyranoside ( 3 J H3‐H4 = 3 J H3‐H2 =3.0 Hz) in the favored 1 C 4 conformation . Similar conformational flexibility could already be demonstrated for the gem ‐difluorocarba‐sugar analog of methyl‐β‐ l ‐idopyranoside . For both 14 and 2 a strong NOE correlations between H2 and H4 as well as between H1 and H5 were observed, indicating a rapid 1 C 4 ↔ 4 C 1 exchange that is not distinguishable on the NMR timescale at room temperature.…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…Conformation equilibrium of xyloside and n-deoxy-n-fluoro-substituted derivatives, bearing naphthyl aglycone, has been explored by R€ onnols et al [105]. Recently, Unione et al [106] investigated the conformational behavior of idose and glucose-like rings by low-temperature NMR experiments. At low temperature, the conformational exchange rate of idose-like rings becomes slow in the 19 F NMR spectroscopic chemical shift timescale.…”
Section: Monosaccharides and Their Derivativesmentioning
confidence: 99%